if f(x) = 7x-1 and g(x) = 4/(x-2), solve fg(x) = x

fg(x) = 7(4/x-2) -1 = x

28/(x-2) - 1 = x

28/(x-2) = x +1

28 = (x+1)(x-2)

28 = x2 - x - 2

0 = x2 - x - 30

0 = (x-6)(x+5)   x=6 x=-5

Answered by Sophie W. Maths tutor

14062 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

A stone, of mass m , falls vertically downwards under gravity through still water. The initial speed of the stone is u . Find an expression for v at time t .


Integrate the natural logarithm of x (ln x) with respect to x


Integrate the expression cos^2(x).


How do I find the maxima and minima of f(x) = e^(x^2)?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences